"Staying on task — how the concept of skill-challenge balance provides a key element to the teaching of the Meisner technique". Issue 2 (3rd July 2021) - Strandberg-Long, Philippa
ABSTRACT: This article presents how the concept of skill-challenge balance — derived from Csíkszentmihályi's theory of Flow — can provide a key factor in the delivery and teaching of the Meisner technique as well as other actor training methods. The American acting practitioner Sanford Meisner's foundational actor training focuses on the redirection of attention, to keep the actor present and less self-conscious. His exercises are presented in a way that encourages external attention to be sustained by using a logical step-by-step process and gradually increasing the difficulty – either when the students' skills develop or when the exercise becomes automated. The article offers evidence that different attentional networks are activated depending on how much attention is directed to task, which rests on the challenge-skill balance being continually adjusted for the actor to sustain task-focus and avoid mind wandering. This demonstrates that finding the balance between skill and challenge in relation to task, while layering the exercises in an extended developmental training-process, is integral to the Meisner method. As an acting tutor, the concept of skill-challenge balance has greatly influenced my own practice, as well as solidified the importance of the teacher's ability to acknowledge the student's understanding and growth. By focusing on the individual and the personal aspect of the skill-challenge balance,  highlights not only the importance of seeing this balance as something fluid – needing constant re-evaluation and adaptation – but also as a something that should be adhered to in any forms of vocational teaching and development. .